1997
DOI: 10.1038/sj.ijo.0800485
|View full text |Cite
|
Sign up to set email alerts
|

Leptin serum levels in normal weight and obese children and adolescents: relationship with age, sex, pubertal development, body mass index and insulin

Abstract: OBJECTIVE: Leptin, the product of the ob gene, is present in higher concentrations in blood of obese subjects than of lean subjects. There is scarce information on the role of leptin in the pathogenesis of human obesity and little is known about leptin serum levels in obese children. DESIGN, SUBJECTS AND MEASUREMENTS: To evaluate the in¯uences of age, sex, pubertal development and weight excess on serum leptin levels, we have studied 390 obese subjects (OS) and 320 normal weight subjects (NWS) aged 5±16 y. Fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
2
8

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 22 publications
(28 reference statements)
5
38
2
8
Order By: Relevance
“…These differences and age-dependence of leptin concentrations become especially evident after appropriate logarithmic transformation (Blum et al 1997). Essentially, there is a significant correlation of leptin, or log-transformed values of leptin, and BMI in healthy males and females of a wide age range (5-77 years) (Isidori et al 2000;Gómez et al 2003;Falorni et al 1997). Contrary to what is expected, there was a lack of a correlation between log-leptin and BMI in adult males with Gal and in our entire adult Gal cohort.…”
Section: Discussioncontrasting
confidence: 58%
“…These differences and age-dependence of leptin concentrations become especially evident after appropriate logarithmic transformation (Blum et al 1997). Essentially, there is a significant correlation of leptin, or log-transformed values of leptin, and BMI in healthy males and females of a wide age range (5-77 years) (Isidori et al 2000;Gómez et al 2003;Falorni et al 1997). Contrary to what is expected, there was a lack of a correlation between log-leptin and BMI in adult males with Gal and in our entire adult Gal cohort.…”
Section: Discussioncontrasting
confidence: 58%
“…These were consistent with previous reports in adults, as well as in children. 31,32,35,36 Studies have demonstrated that leptin may exert part of its function directly on the peripheral lipid metabolism. 20,37 Plasma leptin levels were found to be correlated to plasma lipids, traditionally related to adverse CVD risk, in our present study.…”
Section: Discussionmentioning
confidence: 99%
“…43 Leptin concentration is signi®cantly higher in obese children than non-obese, which suggests that resistance to the effects of leptin may start in early childhood. 43,47 The relationship between plasma leptin and insulin levels is complicated and may be bi-directional. Although plasma leptin concentrations are highly correlated with BMI, insulin levels and insulin sensitivity in humans, 14,15,22 ± 28,38,48,49 it is not yet known whether leptin has a direct effect on insulin sensitivity or if it is only a marker of obesity and related disorders.…”
Section: Discussionmentioning
confidence: 99%